SAFER than SAFE: China Club as a model of a positive after-school initiative. (2nd January 2020) - Cassidy, Claire; Santoro, Ninetta
ABSTRACT: This article reports on a study that investigated the effectiveness of one out-of-school activity: "China Club". China Club, an initiative of Scotland's National Centre for Languages and the Confucius Institute for Scotland's Schools, was established with the central aim of teaching Mandarin language and Chinese culture to young people from a secondary school in the West of Scotland. The article explores the success of China Club against criteria established in 2007 by Durlak and Weissberg to ascertain programme success, that is, how well the programme is: sequenced; active; focused; explicit (SAFE). We took an ethnographic case study approach, complemented by interviews with pupils, teachers and those leading the programme to investigate the effectiveness of China Club. We argue that the China Club has all the elements of a SAFE programme. Further, we suggest that more than these four factors are necessary if an out-of-school initiative is to move successfully beyond academic skills development to the personal and social growth of the individuals involved. We conclude that initiatives must also foster and include the opportunity for the development of effective relationships (R).